Analisis Kadar SGPT (Serum Glutamic Pyruvic Transaminase) Dan Kholinesterase Pada Petani Sayur Di Desa Riang Gede, Kecamatan Penebel, Kabupaten Tabanan - Ni Luh Putu Ari Sukmayanti; Ni Putu Rahayu Artini; Ni Putu Wida Yanti (Universitas Muhammadiyah Surabaya, 2020)
Excessive users in the long term can cause damage to liver function qhich is indicated by the presence of SGPT levels that exceed the reference value and cholinesterase levels that are less than the reference value. The purpose of this study was to determine the levels of SGPT and kholinesterase in vegetable famers in Riang Gede Village, Penebel District, Tabanan Regency. This research is a descriptive study using a statistical test that displays the lowest, highest value, average test results and deviation standards to correct errors in the analysis process. Blood sampling is done on 30 vegetable farmers by using a sampling technique in the form of random sampling SGPT and kholinesterase levels measured using a photometer, the results of the study showed an average SGPT level of 17,0 ± 0,02 U/L, the highest level of 48,0 ± 0,05 U/L and the lowest of 9,0 ± 0,05 U/L. The average level of cholinesterase is 5,9 +0,02 kU/L, the highest level is 8,0 ± 0,05 kU/L and the lowest level is 3,5±0,05 kU/L.